ANALISIS KAPASITAS EMBUNG MONGGOLOMO di KABUPATEN GORONTALO - Hamdan Baderan (Jurnal Teknik Sipil, Arsitek, Perencanaan Wilayah (J-TSIAP), 2023)
The aim of this research is to determine the need for raw water in North Isimu Village for the next 25 years from 2011 - 2035 and also to determine the capacity of the Monggolomo Embung in fulfilling raw water in North Isimu Village in 2011 - 2035. This research uses a literature study method which is part from qualitative research. Literature study is to collect data related to concepts, approaches, procedures and research data analysis. The literature in the research comes from literature in the form of books, scientific journals and documents from agencies, namely the River Region Office and the Gorontalo Regency BPS Office. The research results show population projections for 25 years (2011 - 2035) using the base year (2009/2010) and analysis of raw water needs for residents of Isimu Utara Village, Tibawa District shows that the greater the population, the greater the amount of raw water needed. The projected population in 2034 is 3038 people with water needs of 7,595 m³/day for an average calculation of 60 liters/jia/day. Monggolomo Reservoir can be sufficient to meet the raw water needs of North Isimu Village until 2035. Addressing the fulfillment of raw water/clean water in North Isimu Village, which mostly uses dug wells and river water, both for drinking water purposes. So it is necessary to develop the use of the Monggolomo Reservoir as a source of clean water for the residents of North Isimu and its surroundings.